Role overload, workplace norms and employee's safety performance : the mediating role of time-based work-familiy conflict - Natalie Inez, Juim (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The main purpose of the study is to examine the mediating effect of time-based workfamily conflict on the relationship between role overload, workplace norms and employee’s safety performance.This study was conducted in Sarawak. Questionnaires were distributed to 213 employees in private sector in three different industries which arehealthcare, construction and Oil & Gas in Kuching and Miri area. Data was collected through 30 items questionnaires on a five-point Likert Scale. Both descriptive and inferential statistics were used to analyze the data using the Statistical Package for Social Science (SPSS) version 18. Correlation analyses were conducted to test the relationship between role overload and workplace norms with safety compliance and safety participation; whereas descriptive analysis was conducted to analyze demographic characteristics of respondents. Besides that, regression and Sobel Test were also used in this study. Findings reveal that there is a significant relationship between role overload, workplace norms with safety performance. It was also found that time-based work-tofamily conflict mediates the relationship between role overload and workplace norms with safety performance however family-to-work were not. Organizations can use the information from this study to discover how to decrease work-family conflict.Organization should create more supportive working environment rather than stressful workplace norms and role overload to lower employee’s work-family conflict and will leads their compliance and participation in safety activities in the workplace.